2020
DOI: 10.1088/1361-6528/ab73b9
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical and magnetic properties of Y3−0.02−xEr0.02Yb x Al5O12 (0 < x < 0.20) nanocrystals: effect of Yb content

Abstract: The paramagnetic Y3−0.02−x Er0.02Yb x Al5O12 (x = 0.02, 0.06, 0.10, 0.12, 0.18, 0.20) nanocrystals (NCs) were synthesized by the microwave-induced solution combustion method. The XRD, TEM and SEM techniques were applied to determine the NCs’ structures and sizes. The XRD patterns confirmed that the NCs have for the most part a regular structure of the Y3Al5O12 (YAG) phase. The changes of the distance between donor Yb3+ (sensitizer) and acceptor Er3+ (act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Combustion relies on rapid oxidation that generates heat or as a sequence of exothermic chemical reactions between a fuel and an oxidant that is accompanied by the production of heat and the conversion of chemical species [85][86][87][88]. In the volume reaction model, also referred to as thermal explosion, the entire sample is uniformly heated to the ignition temperature, and the combustion reaction coincides in all parts of the sample.…”
Section: Microwave-assisted Combustion (Mac)mentioning
confidence: 99%
See 2 more Smart Citations
“…Combustion relies on rapid oxidation that generates heat or as a sequence of exothermic chemical reactions between a fuel and an oxidant that is accompanied by the production of heat and the conversion of chemical species [85][86][87][88]. In the volume reaction model, also referred to as thermal explosion, the entire sample is uniformly heated to the ignition temperature, and the combustion reaction coincides in all parts of the sample.…”
Section: Microwave-assisted Combustion (Mac)mentioning
confidence: 99%
“…The microwave-assisted combustion makes the synthesis even faster, in the order of tenths of seconds (Figure 8). [85,90] with permission from The Royal Society of Chemistry.…”
Section: Microwave-assisted Combustion (Mac)mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Al 5 O 12 (with Ln 3+ = Ho 3+ , Tb 3+ or Tm 3+ ) for the host matrix and the lanthanidedoped garnets, respectively. The selection of the composition (Y 3−x−y Ln x Yb y Al 5 O 12 with x = 0.03 and y = 0.3) is based on studies on YAG structures reported in the literature for which efficient upconversion responses were obtained (Liu et al, 2007;Mishra et al, 2014;Kamińska et al, 2020). The samples are respectively referenced as YAG, HoYAG, TbYAG, and TmYAG.…”
Section: Synthesis Of Lanthanide-doped Garnet Nanospheresmentioning
confidence: 99%
“…The interest in upconverting yttrium aluminum nanoparticles is increasing (Diaz-Torres et al, 2005;Li et al, 2005;Liu et al, 2007;Jain et al, 2018;Kamińska et al, 2020) because these materials can find applications in a wide variety of fields such as biomedicine, encoding, sensors, energy, security, and so on (Van der Ende et al, 2009;Chen and Xiaojun Zhao, 2012;Chen et al, 2014;Wang et al, 2015;Zhou et al, 2015;Kłonkowski et al, 2018). In this context, there is plenty of room for new materials based on lanthanide-doped YAG nanogarnets with upconversion properties.…”
Section: Introductionmentioning
confidence: 99%